2007
DOI: 10.1007/s10803-007-0463-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Use of Visual Strategies in Play Groups for Children with Autism Spectrum Disorders and their Peers

Abstract: The purpose of this study was to investigate the impact of visual strategies with preschool children with autism spectrum disorders (ASD) and their peers during play group sessions. A changing-criterion design was implemented with three preschool-aged children with ASD while they participated in play groups with four typically-developing peers. Results indicated improvements in the use of script phrases, context-related comments, and intervals in which speech occurred for all three participants. Results regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 27 publications
4
46
0
6
Order By: Relevance
“…In the current study, VI appeared equally effective with in vivo modeling and SP, which was a surprising finding since it has been well reported that individuals with autism usually face difficulties when instructed verbally [15,83]. A possible explanation might be that the predominant instructional method in the current school was the use of VI alongside some picture applications (e.g.…”
Section: Discussionsupporting
confidence: 55%
“…In the current study, VI appeared equally effective with in vivo modeling and SP, which was a surprising finding since it has been well reported that individuals with autism usually face difficulties when instructed verbally [15,83]. A possible explanation might be that the predominant instructional method in the current school was the use of VI alongside some picture applications (e.g.…”
Section: Discussionsupporting
confidence: 55%
“…The most commonly employed visual supports were Social Stories (e.g., Sansosti and Powell-Smith 2008;Scattone 2008;Thiemann and Goldstein 2001), scripts (e.g., Ganz and Flores 2008;MacDuff et al 2007), and visual activity schedules (e.g., Betz et al 2008). Visual supports were also used in tandem with other intervention types, including ABA (e.g., Crozier and Tincani 2007), peer training (e.g., Ganz and Flores 2008;Kohler et al 2007), and video modeling (e.g., Sansosti and Powell-Smith 2008;Scattone 2008). Overall, the studies using visual supports had positive findings, suggesting they can be an effective method for enhancing social understanding and structuring social interactions or communication for preschool and school-aged children with autism.…”
Section: Visualmentioning
confidence: 99%
“…Post hoc data analysis included additional coding of the PD utterances as Scripted (S), Related (R) or Novel (N) conceptually based on Ganz and Flores (2008). Reliability coding was completed on 25% of the transcriptions with 92% agreement.…”
Section: Response Definition and Reliabilitymentioning
confidence: 99%
“…Video Modeling (Maione and Mirenda 2006;MacDonald et al 2009), graphic symbols (Johnson et al 2003), and scripts (Ganz and Flores 2008;Goldstein and Cisar 1992) have all demonstrated positive results for participants with ASD. Recently, Ganz and Flores (2008) investigated the use of visual cues within dramatic playgroups for preschoolers with ASD. Written scripts with picture cues were utilized to teach verbal utterances related to themes (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation